Beneficial Effects of Qili Qiangxin Capsule on Lung Structural Remodeling in Ischemic Heart Failure via TGF-β1/Smad3 Pathway - He, Yaoyao (Evid Based Complement Alternat Med, 2015)
Qili qiangxin (QL) capsule is a traditional Chinese medicine that is widely used for the treatment of patients with chronic heart failure (CHF) of all etiologies, although the exact mechanisms of action remain unclear. CHF leads to pulmonary vascular remodelling and thickening of the alveolar-capillary barrier that may be important mechanisms in the poor clinical outcome in patients with end-stage heart failure. We examined whether QL could improve lung injury in ischemic CHF by reducing lung remodeling. Rats with myocardial infarct received QL (1.0 g/kg/day) for 4 weeks. Echocardiographic and morphometric measurements were obtained followed by echocardiography, histological staining, and immunohistochemical analysis of lung sections. CHF caused significant lung structural remodeling evidenced by collagen deposition and thickening of the alveolar septa after myocardial infarct that were greatly improved by QL. Lung weight increased after infarct with no evidence of pulmonary edema and was normalized by QL. QL also reduced lung transforming growth factor-β1 (TGF-β1), p-Smad3, tumor necrosis factor-α (TNF-α), and Toll-like receptor-4 (TLR4) expression. Thus, QL reduces lung remodeling associated with CHF, mainly by suppressing the TGF-β1/Smad3 signaling pathway. The mechanism may also involve inhibition of TLR4 intracellular signaling.